Predictive Value of Naples Prognostic Score in Determining the Prognosis of Acute Pancreatitis—A Single-Center Experience - Fatih Sargin; Zeynep Gok Sargin; Ahmet Caliskan; Ayse Karaduru Avci; Celal Dogan; Ali Avci (Journal of Clinical Medicine, 2026)
Background/Objectives: The Naples Prognostic Score (NPS) is a composite index of nutritional and inflammatory status that has demonstrated prognostic value across various critical illnesses. This study aimed to evaluate the prognostic significance of NPS in patients with acute pancreatitis (AP). Methods: In this retrospective cohort study, 452 patients diagnosed with AP between January 2024 and March 2026 were classified as mild (MAP), moderately severe (MSAP), or severe (SAP) according to the revised Atlanta classification. NPS was calculated from admission serum albumin, total cholesterol, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio. Results: Of the 452 patients, 276 (61.1%) had MAP, 124 (27.4%) had MSAP, and 52 (11.5%) had SAP. NPS was significantly higher in SAP patients than in MAP and MSAP patients (for both comparisons; p < 0.001). ROC analysis showed an AUC of 0.758 (95% CI: 0.693–0.824) for predicting SAP, with an optimal cut-off of NPS ≥ 3 yielding a sensitivity of 80.8% and a specificity of 61.3%. Patients were stratified into low (0–2) and high (3–4) NPS groups. High NPS was significantly associated with SAP (χ2 = 33.044, p < 0.001), with a negative predictive value of 96.1%. In multivariable analysis, high NPS was an independent predictor of SAP (OR: 4.346, 95% CI: 2.018–9.362; p < 0.001). Conclusions: NPS, calculated from four routine laboratory parameters available at admission, is a simple, rapid, and independent predictor of disease severity in AP and may support early risk stratification in the emergency setting.